Al-Qusyairi Perspektive Education in Reduction of Moral Decline - Sapdi, Rohmat Mulyana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Moral education is very much needed in Indonesian education, given the still high moral crisis facing this Muslim-majority country. Today, human life is far from the values of the Al-Quran and Hadith. Human life has become more materialistic, individualistic, and spiritually deficient. This study aimed to study the moral education concept explained by Imam Qusyairi in the Book Risalah Al-Qusyariyah and its implementation in reducing moral decline. This research is a Library Research with a qualitative descriptive approach by collecting library materials related to the research focus. The Risalah Al-Qusyairi book has some applications of the values of education, learning, and guiding students to have increased faith, obedience, and justice in life. Imam al-Qusyairi's concept of moral education must be applied to all aspects of learning and daily life, especially in the present, which is slowly destroying the human soul. By embodying the concept of AL-Qusyairi moral education, a person will respect and appreciate teachers for providing learning materials and making friends with their peers, practicing good morals, doing charity, and trying their best to leave bad morals.